Linear circuit analysis : time domain, phasor and laplace transform approaches / Raymond A. DeCarlo, Pen-Min Lin. - DeCarlo, Raymond A. (The Oxford series in electrical and computer engineering, 2001)
This text is designed as a standard introductory electric circuits course. It covers all of the standard topics in a traditional order, includes case studies, and extensive use of modern computer packages, SPICE & MATLAB for problem solutions